Fifth Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations. (Policy Papers; Policy Paper, 2012)
Periodic Monitoring Reports update the status on Management Implementation Plans (MIPs) in response to Executive Board-endorsed IEO recommendations. The last Periodic Monitoring Report (PMR) was discussed by the Board Evaluation Committee (EVC) and then agreed by the Board in August 2011. That report concluded that all key performance benchmarks related to the MIPs covered in that report had either been met or were on track for timely completion, that no new remedial actions were proposed, and that there were no outstanding performance benchmarks to be reviewed in the next PMR. In their assessment to the Executive Board, the EVC did, however, note that further work was needed on three other issues-staff mobility, enhanced coverage of previous implementation plans, and the process for following up on IEO recommendations. This fifth report therefore updates work on these three issues, including a consolidated picture of recent progress on all Board-endorsed recommendations made since the first PMR in 2007. This PMR also presents progress on the Implementation Plan in response to Board-endorsed recommendations arising from the IEO Evaluation of IMF Interactions with Member Countries (hereafter, Interactions Evaluation).